Сегрегация признака «окраска венчика» в инбредных потомствах розовоцветковой крупноплодной земляники (Fragaria × ananassa Duch.) - Батурин, С.О.; Кузнецова, Л.Л. (Фактори експериментальної еволюції організмів, 2013)
Aims. The study of the nature of inheritance pink color corolla in inbred offsprings F. × ananassa. Methods. I₁ generations seedlings obtained from commercial, pink flowering, Dutch hybrid F1 C141 (2n = 8x = 56) were material of the study. The model with chromatid type of gene segregation of alleles based on hypergeometric frequency gametes autopolyploids distribution, in particular, the octoploid strawberry was used for interpretation of the character trait segregation in seed offsprings. Results. The variability of corolla color intensity from light pink to deep red was revealed among pink flowering inbred progeny seedlings. The intensity of coloring depends on the number of dominant alleles that control the synthesis of anthocyanidins in the petals of a flower. The experimental data are in good agreement with the theoretically expected. Conclusions. Using the model of monogenic inheritance of the «corolla color» trait with chromatid segregation that predicts the share of hybrid seedlings of the desired color of the corolla in directional crossings, thereby maintaining effective selection for the decorative qualities and productivity.

Key words: Fragaria × ananassa, octosomic inheritance, pink-flowering cultivar, inbreeding, selection.